Hubungan Antara Dukungan Sosial Suami Dengan Kepercayaan Diri Ibu Dalam Pemberian Asi Eksklusif Di Puskesmas Colomadu I - Takariyana, Annisa; , Dra. Zahrotul Uyun, M.Si (2016)
This research goal to determine the relationship between social support husband with the confidence of mothers in exclusive breastfeeding. Samples from this research are 88 women who came to the Posyandu in the area Puskesmas Colomadu 1. The sampling technique of this research using accidental sampling technique. The method used in this research is quantitative method using a measuring instrument the scale of social support husband and the scale of confidence in exclusive breastfeeding mothers. The data analysis technique used is the correlation of Pearson Product Moment. Based on the analysis of data obtained by the value of the correlation coefficient (r) of 0,556 with sig. = 0,000; p <0,01 ; which means there is a significant positive relationship between social support husband with the confidence of mothers in exclusive breastfeeding. The effective contribution of social support husband to the mother's confidence in exclusive breastfeeding is equal to 30,91%, 69,09% so there are still other factors that affect the mother's confidence in exclusive breastfeeding. Keywords: social support husband, self-confidence, exclusive breastfeeding.